Cheating in online exams at Australian universities - E, Smith,; L, Clarke,; P, Carmona, (IJRDO- Journal of Educational Research, 2017)
In recent years an ever increasing number of universities have started to offer online degrees. In Australia most universities offer online degrees, however, this study will take a closer look at an organisation which offers the largest selection of online courses. For the purposed of this study the organisation will be referred to as “online degree providers” (ODP). Along with this new method of completing degrees comes new forms of academic dishonesty and misconduct. Academic dishonesty and misconduct among students is not a new phenomenon. As universities around Australia and the world are offering an increasing number of courses and degrees online, it is important to plan how to deal with the problem of academic dishonesty and misconduct. In 1990, the American Council on Higher Education reported that cheating at was on the rise at universities in the United States (US). In recent years, there has been a great deal of research in the area of academic dishonesty, most of which almost exclusively focused on the US. This research considers academic dishonesty broadly, the focus of the paper is on cheating in online exams. Other sorts of academic dishonesty, for example plagiarism or employing assignment-writing companies, are beyond the scope of this paper. With many courses using an end-of-subject exam for up to 60% of the student’s overall mark for the subject, it is vitally important that cheating in exams be addressed. This paper contributes to the limited research literature on academic dishonesty and misconduct in online programs and online exams at Australian universities by taking a close look at what academic dishonesty and misconduct is and how it is happening. It is important that these questions be understood because, students who cheat at university are more likely to become professionals who in the future will engage in illegal, unethical or immoral behaviours in the workplace.